Rheological and mutritional characterization of sweet corn by-product (Cob) to develop a functional ingredient applied in dressings - Castillo, Sandra; Rodríguez, Alexis; Bautista Villarreal, Minerva; García Solano, Nallely; Gallardo Rivera, Claudia Tomasa; Báez González, Juan Gabriel; Sánchez García, Eduardo; García Alanís, Karla G. (Frontiers Media, 2021)
In this study, a flour from corn cob (central core of the maize ear, stage R4) was obtained through three treatments. Thethreeflours obtainedwerecharacterizedbybromatological analysis, yield, and granulometry. Additional dressing-type oil in water (O/W) emulsions were developed, varying the formulation by incorporating distinct amounts of corn cob f lour. The formulations’ stability was evaluated over a period of 21 days, determining the particle size, creaming index, coalescence rate, consistency coefficient (k), and f low behavior indices (n). Results have shown significant differences in protein, fat, and carbohydrate content in the flour, depending on the cooking treatment. A good percentage of grinding yield was obtained (98%), in addition to several fractions by granulometry (60, 120, 250 MESH), showing differences in their nutritional content. Finally, the particle size of O/W emulsions developed varied among formulations. The combination of 0.6% of xanthan gum (XG) and corn cob flour showed major stability in average droplet size. No significant differences were observed in the coalescence rate values for the three formulations. Still, significant differences in the creaming index were evidenced in those formulations without XG or corn cob flour. The results regarding the consistency coefficient (k) and flow behavior indices (n) suggest a possible synergy between XG and flour of corn cob for enhancing the viscosity and pseudoplasticity of dressings in a concentration-dependent manner.